ANALISIS PENGARUH PENERIMAAN PAJAK PENGHASILAN PASAL 25/29 ORANG PRIBADI DAN BADAN TERHADAP TOTAL PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN KOTA - Siahaan, Yannuke Patricia; Butarbutar, Monetarist; Girsang, Edwin Harapan (JURNAL PROINTEGRITA, 2020)
This study aims at providing empirical evidence about the effect of Personal and Corporate Income Tax Article 25/29 revenue on total tax revenue in Tax Office of Medan City. On this study, there are 2 independent variables which are Personal Income Tax Article 25/29 Revenue and Corporate Income Tax Article 25/29 Revenue. The sampling method is purposive sampling that based on author’s criteria which has been determined before. The population on this study is all of the Personal Income Tax Article 25/29 Revenue, Corporate Income Tax Article 25/29 Revenue and Total Tax Revenue that have been collected by Tax Office Of Medan Kota since January 2002 until December 2018 which is 192 and the amount of samples is 30. Hypotheses in this study are tested by descriptive statistic and multiple regression analysis method, with the regression equation is 91.908.356.751,180 + 0,253X1 + 2,576X2. To analyze the multiple regression on this study method, the author uses Statistical Product and Service Solution (SPSS) Version 25.0 For Windows with the F Test (ANOVA) and T Test (partial). The result of The F Test shows that all of independent variables simultaneously do not affect total tax revenue, as the amount of effect is only 6,5% based on The Determination Test. Based on The T Test, Personal Income Tax Article 25/29 revenue and Corporate Income Tax Article 25/29 revenue do not have effect on Total Tax Revenue.